MENINGKATKAN PRESTASI BELAJAR IPS MATERI PENCEGAHAN PENYIMPANGAN SOSIAL MELALUI PENERAPAN MODEL PEMBELAJARAN TERSTRUKTUR PADA SISWA KELAS VII.1 SMP NEGERI 11 BINJAI TAHUN PELAJARAN 2018 / 2019 - Surya Dharma Tarigan (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
Before carrying out teaching and learning activities, teachers need to make teaching preparations or Recana Learning Implementation (RPP) in order to implement some of the monthly plans and annual plans. In preparation it is already contained about, the purpose of teaching, the material to be taught, teaching methods, lesson materials, learning model props, and evaluation techniques used. Therefore every teacher must understand correctly about the purpose of teaching, specifically choosing and determining teaching methods according to the goals to be achieved, how to choose, determine and use props, how to make tests and use them, and knowledge of evaluation tools. Problem-based research, (a) Does structured learning with assignments affect the learning outcomes of Social Knowledge? b) How does structured learning affect students' learning motivation? The purpose of this action research is: (a) To uncover the influence of structured learning models on the learning outcomes of Social Knowledge. (b) To uncover a structured learning model for the motivation of social knowledge learning of Grade VII.1 students of SMP Negeri 11 Binjai. This study uses action research as many as three rounds. Each round consists of four stages: design, activities and observations, reflections, and reflections. The target of this study was students of Grade VII.1 SMP Negeri 11 Binjai. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysts obtained that students' learning achievements improved from cycle I to cycle III, namely, cycle I (67.74%), cycle II (77.41%), cycle III (96.77%). The conclusion of this study is that the structured learning model can have a positive effect on the learning motivation of Smp Negeri 11 Binjai students, and this learning model can be used as an alternative to social knowledge learning in junior high school.